GUIDELINES FOR A COMPREHENSIVE PLAN ON SUSTAINABLE MANAGEMENT, MANAGEMENT AND PROTECTION OF WATER RESOURCES, COASTAL SPACE IN EL COCO, NICOYA PENINSULA, COSTA RICA - Orias-Arguedas, Lidia (2016)
This document is the continuation of the article entitled: “The Expansion of El Coco Coastal Urban Space and Its Relationship with Vulnerability to Pollution of Water Resources, Nicoya Peninsula, Costa Rica,” included in the Central American Geographic Magazine, Issue No.50, I Semester 2013. The conditions of water resources in El Coco urban coastal space are questioned depending on factors, categories, impact indicators, vulnerability ranges, and those involved in the decision-making process. The proposal seeks to articulate, in the figure of a Comprehensive Plan of Water Resources Management, two programs with guidelines and strategies. The first one refers to sustainable management, control systems, and administrative management of water resources. The second program refers to the importance of developing a project to amend the legislation on water resources in coastal areas and public institutional management.